P90 Catch – Community Access To Ct Chest. (10th November 2014) - Moorcroft, CS; Kamalatharen, G; Elliot, S; Walsham, A; Sharman, A; Taggart, SCO
Abstract : Introduction: Rates of lung cancer diagnosis for two week wait (2WW) referrals are low although referrals are increasing. Many 2WW's are potentially exposed to unnecessary anxiety as the referral requires the G. P. to inform the patient of the possibility of cancer. CATCH (C ommunity A ccess T o CT Ch est) is a new protocol of care that has been developed by the Salford lung cancer team in collaboration with the Salford C. C. G. whereby abnormal "low risk" CXR reports are communicated to G. P.s with instructions for them to request a CT scan, which is then fast tracked allowing rapid performance and reporting of the scan with appropriate advice to the GP. Methods: A d-base was set up to capture the performance of CATCH from its introduction on 05.02.2014 to 05.07.2014. Demographic details were collected for dates of CXR, CXR report, CT request, CT report, relevant outcomes and 2WW activity for same time (2011–2014). Participating patients were interviewed by telephone using a structured questionnaire (supported by a postal questionnaire for non-responders). Results: 53 patients underwent an abnormal CXR with advice to enter into the CATCH protocol and of these 7 bypassed CATCH having been referred directly into the 2WW system by their G. P.s. For the 46 patients completing CATCH, seven (15%) urgent 2WW referrals were recommended. In the remaining 39 patients, 28 required no follow up, 9 non-urgent referral to the chest clinic and 2 repeat community CXRs. Timelines for performance of CT scans were acceptable (see Table ) and detected cancer in 5/46 (10.9%) and were normal in 8/46 (17.4%). 23–26 patients interviewed to date rated the service overall as either very good or excellent. During same points in 2011, 2012, 2013 and 2014 2WW numbers were 69, 84, 89 and 81 respectively. Conclusions: Our provisional data support the role of CATCH as a new system of care for managing "low risk "CXR reports that might otherwise be referred into growing 2WW clinics. Thus far, the protocol moves at a rapid pace and has been well received by the patient (although we await the results of the postal survey in due course).